Phenomenon of Demikhov. In the 1st Moscow Medical Institute named after Sechenov (1956–1960). V.P.Demikhov's first business trip to Germany (December 1958 – January 1959) A Round Table discussion for the newspaper "Stuttgarter Zeitung" (March 1959) - S. P. Glyantsev (Трансплантология (Москва))
.